Animal Health Protection – Assessing Antimicrobial Activity of Veterinary Disinfectants and Antiseptics and Their Compliance with European Standards: A Narrative Review - Tyski Stefan; BOCIAN EWA; LAUDY AGNIESZKA E. (Polish Journal of Microbiology)
Disinfectants and antiseptics lead in reducing the number of microorganisms, including pathogenic ones, thus limiting the number of infections. In the veterinary field, disinfection prevents the transfer of pathogenic microorganisms from animals to humans and vice versa, as well as among animals. Several assays of disinfectant antimicrobial activity testing, often not standardized, without appropriate controls, and not validated, have been used and published. To unify these methods, nine European Standards (ENs) for the veterinary area have been prepared. These tests make it possible to examine whether a given disinfectant has bactericidal, fungicidal, or virucidal activity by the standard. This publication discusses ENs regarding the assessment of the above-mentioned antimicrobial activity of disinfectants used in veterinary medicine. Recent research on this topic has also been cited. According to ENs, tests are carried out using the suspension method or carriers in clean and dirty conditions. The decontamination of high-risk animal and zoonotic pathogens is also discussed. Selected publications on cattle, pig, poultry, and aquaculture farm disinfection are presented. Only valid methods of the described studies with appropriate statistical analysis can prove adequate antimicrobial activity. So far, the role of international standards in investigating the antimicrobial activity of disinfectants and antiseptics to reduce infections has been underestimated. This publication highlights gaps and irregularities in conducted research and aims to inform about existing EN standards dedicated to testing the biocidal activity of disinfectants and antiseptics intended for use in the veterinary area.